2022
DOI: 10.1111/wej.12785
|View full text |Cite
|
Sign up to set email alerts
|

Optimized one‐pot synthesis of CdSe quantum dot capped with 3‐mercaptopropionic acid as an efficient fluorescent probe for selective detection of Hg (II)

Abstract: Here, we demonstrated the use of 3‐mercaptopropionic acid‐capped CdSe quantum dots (CdSe QDs) for the sensing of mercury ions (Hg2+) in solution. The size and the shape of the synthesized QD were observed through transmission electron microscopy (TEM), and crystallinity was confirmed through X‐ray diffraction (XRD) analysis. The synthesized QD showed to have mean size 4 nm. Our QD was found to sense Hg2+ ions with a detection limit of 5 ppm at pH 7.0 and a linearity range of 5–50 ppm. The effect of pH on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…To modify the thiol capped-QDs according to the specific target, the free carboxyl site associated with the encapsulating layer of QDs are mostly coupled with amine-containing molecules (amino acids, peptides, etc.). Thioglycolic acid (TGA), 51 glutathione (GSH), L-cysteine (Cys), 52 and mercaptopropionic acid (MPA) 15,53 are the commonly used coatings among the thiols for the direct preparation of thiol-capped QDs. 54 Wang et al 55 showed a simple approach for sensing As 3+ using GSH-capped CdTe QDs.…”
Section: Surface Capping Of Qdsmentioning
confidence: 99%
See 2 more Smart Citations
“…To modify the thiol capped-QDs according to the specific target, the free carboxyl site associated with the encapsulating layer of QDs are mostly coupled with amine-containing molecules (amino acids, peptides, etc.). Thioglycolic acid (TGA), 51 glutathione (GSH), L-cysteine (Cys), 52 and mercaptopropionic acid (MPA) 15,53 are the commonly used coatings among the thiols for the direct preparation of thiol-capped QDs. 54 Wang et al 55 showed a simple approach for sensing As 3+ using GSH-capped CdTe QDs.…”
Section: Surface Capping Of Qdsmentioning
confidence: 99%
“…). Thioglycolic acid (TGA), 51 glutathione (GSH), l -cysteine (Cys), 52 and mercaptopropionic acid (MPA) 15,53 are the commonly used coatings among the thiols for the direct preparation of thiol-capped QDs. 54 Wang et al 55 showed a simple approach for sensing As 3+ using GSH-capped CdTe QDs.…”
Section: Preparation Of Water-soluble Qdsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant obscuring of fluorescence was thought to be a sign of the selection of Hg 2+ ion. 221 Two structures of CdSe/ZnS CQDs, with varying solubility characteristics, were synthesized by Gilma Granados-Oliveros et al to detect Hg 2+ ions. In the first structure, CdSe/ZnS CQDs were capped with oleic acid (CdSe/ZnS/OA).…”
Section: Photophysical Properties Of Cqdsmentioning
confidence: 99%